Preliminary Report on the Defense of Indigents in Missouri - Jules B. Gerard (Washington University Law Quarterly, 1964)
Last year the American Bar Foundation, in cooperation with the American Bar Association and other groups, launched a nationwide audit of the defense of indigent persons accused of crime. Information was gathered from every state. Within each state, questionnaires were mailed to most judges, all prosecuting attorneys, and a sampling of defense lawyers, and field surveys were conducted in several counties selected at random. One or more reporters, usually native lawyers presumably familiar with the state's administration of criminal law, interviewed the judge, the prosecuting attorney, the magistrate, and, if there was one, the public defender, in each survey county. They also prepared detailed analyses, called “docket studies,” of a random sampling of the criminal cases processed by the survey counties in 1962. The end product should be the most comprehensive compilation of data about the administration of criminal law yet attempted in the United States. This Article is a preliminary report on the data collected in Missouri.
Keywords: Public legal service; Legal aid